Differences in the Offensive and Defensive Actions of the Goalkeepers at Women’s FIFA World Cup 2011 - Sainz de Baranda, Pilar; Adán, Laura; García-Angulo, Antonio; Gómez-López, Maite; Nikolic, Brittany; Ortega-Toro, Enrique (Frontiers in Psychology, 2019)
The aim of this study was to analyze the technical and tactical offensive and defensive actions of the goalkeepers and to determine the relationship between these actions and the qualifying results of their respective teams. The sample studied is made up of the goalkeepers (n = 20) of the senior national teams that participated in the FIFA Women’s World Cup in Germany 2011. A descriptive analysis was developed comparing the offensive and defensive actions in competition carried out by the goalkeepers on qualified teams (pass the group stage) with the goalkeepers on unclassified teams (not pass the group stage). For the inter-group comparison, the value of the coefficient of variation was incorporated and the effect size calculated. All data were treated with a statistical significance level of p < 0.05. The results show that the goalkeepers on qualified teams have higher offensive registers, as well as a higher number of passes successfully completed in different areas of the field. The goalkeepers on unclassified teams show higher defensive records such as saves inside the area, foot stops and wrong clearances among others.